Дослідження підходів до сумаризації для українських текстів - Кардаш, Д. М. (ХНУРЕ, 2024)
The problem of textual data summarization in the Ukrainian language in the context of computational linguistics is studied. The aim of the study is to evaluate and compare different approaches to language modeling for the Ukrainian language. The work includes creating a data corpus, analyzing existing methods, conducting experiments with different language units, and evaluating the resulting models. In particular, the paper discusses the main areas of linguistics, such as phonology, morphology, syntax, semantics, and pragmatics, which form the theoretical basis for computer text processing.
Keywords: The problem of textual data summarization; сумаризація